Reflection on the pharmaceutical service in nursing homes; understanding reality to cover needs - Juan F. Peris-Martí; Elia Fernández-Villalba; Patricia Bravo-José; Carmen Sáez-Lleó; María García-Mina Freire (Elsevier, 2016)
The increasing concern regarding chronic care, which is a consequence of the current demographic progression, and the need to decrease the costs associated with its care, places a focus on social care homes caring for highly dependent patients. Simultaneously, the residential facilities are progressing in order to care for fragile patients with increasingly complexity, even though, with some exceptions, it is in parallel with the healthcare system. Within this reality, pharmaceutical care is developing very differently in all the autonomic regions, and has become a reason for controversy. In this sense, diverse factors related with the patient care setting, but also linked to different pharmaceutical levels, make it difficult to implement a patient care model. Faced with this scenario, it seems reasonable to analyze the situation from the perspective of the healthcare requirements of the institutionalized persons in these facilities, and in terms of the patient care that we can and should provide; subsequently, and based on this, we should be able to propose the basic guidelines for developing an efficient model of pharmaceutical care integrated within this patient care setting